Machine Learning Analysis in Mechanical Engineering - Zhao, Huangyu (Computers and Artificial Intelligence, 2024)
Despite the rapid development of the AI industry and the programming industry in the machinery manufacturing or production industry, there is no systematic explanation as to why the use of machine learning can enhance the development of related industries. This paper summarizes the reasons for the industry’s development direction from the three aspects of machine learning’s automation design, expected maintenance, and production efficiency improvement. The learning types are briefly introduced to indicate the application of machine learning in mechanical engineering. By providing relevant examples, the superiority of machine learning in mechanical engineering is reflected, and specific practical cases are given to show the development trend of machine learning in the manufacturing industry in the future. Finally, we make predictions on the main development directions of machine learning in the future industry.